Holmograptus spinosus and the Middle Ordovician (Darriwilian) graptolite biostratigraphy at Les Méchins (Quebec, Canada) - Maletz, Jörg (Canadian Journal of Earth Sciences, 2009)
The Les Méchins region in Quebec provides a unique opportunity to understand the Darriwilian graptolite succession in eastern North America. The graptolite faunas of the upper member of the Anse au Crapaud Formation include the Arienigraptus gracilis , Oncograptus upsilon , Undulograptus austrodentatus , and Holmograptus spinosus biozone faunas and, thus, complement the well known Darriwilian faunas of the Cow Head, Table Head, and Goose Tickle groups of western Newfoundland. In particular, the Holmograptus spinosus Biozone interval of calcarenitic limestones bears a rare combination of benthic (shelly) and planktic (graptolitic) faunas with conodonts, brachiopods, ostracods, sponge spicules, and algal remains associated with common graptolites that allow an inter-continental correlation. The Holmograptus spinosus Biozone is introduced for the interval based on a diverse and characteristic graptolite fauna. The fauna includes among others, Atopograptus woodwardi , recognized for the first time in North America. The Holmograptus spinosus Biozone fauna can be found worldwide and is easily correlated into the conodont biofacies using species of the genus Histiodella . Ties between graptolite and conodont biozonations are discussed for the Darriwilian. Silicified ostracods are illustrated for the first time from the interval. Hustedograptus quebecensis is described as new.